1997
DOI: 10.1007/bf02815130
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive pattern of Bergmann glial pathology in human hepatic encephalopathy

Abstract: Alzheimer type II astrocytosis is the pathological hallmark of hepatic encephalopathy. These astrocytes undergo a characteristic morphological change and, in addition, lose immunoreactivity for glial fibrillary acidic protein (GFAP). However, a previous study in the portacaval shunted rat, a model of hepatic encephalopathy, revealed increased rather than decreased GFAP immunoreactivity in Bergmann glia, a specialized group of cerebellar astrocytes. In the present study, sections of cerebellar vermis from 15 ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…This is in accordance with previous studies, since in the portacaval shunted rat model increased GFAP immunoreactivity was found in Bergmann glia, specialized cerebellar astrocytes (29), and decreased in frontal cortex (7). On the other hand, GFAP expression in Bergmann glia in human liver cirrhosis was not found to be altered, thus indicating that the course of HE affects GFAP expression (30). FIN pretreatment reduced the expression of GFAP in the hippocampus and the cortex, further suggesting its protective role on astrocytes in HE.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with previous studies, since in the portacaval shunted rat model increased GFAP immunoreactivity was found in Bergmann glia, specialized cerebellar astrocytes (29), and decreased in frontal cortex (7). On the other hand, GFAP expression in Bergmann glia in human liver cirrhosis was not found to be altered, thus indicating that the course of HE affects GFAP expression (30). FIN pretreatment reduced the expression of GFAP in the hippocampus and the cortex, further suggesting its protective role on astrocytes in HE.…”
Section: Discussionsupporting
confidence: 92%
“…Exposure to lead before development of the brain revealed a lower level of expression of mRNA for GFAP. GFAP expression is also lowered by human hepatic encephalopathy (Kimura and Budka, 1986;Kril et al, 1997). Although these studies show the possibility of pathological reductions in the expression of GFAP, it remains to be determined whether depression might be associated with environmentally altered expression of GFAP.…”
Section: Discussionmentioning
confidence: 94%
“…While astrocytes lose their immunereactivity to GFAP, Bergmann glia in PCA rats shows an increase in GFAP immunereactivity, but in EH patients changes in GFAP immunereactivity are not detected. 5,6 Previous studies in six-month PCA rat model showed an increase in astrocyte swelling and a vacuolization in the cerebellum. 27 Additionally, microglia activation and astrocyte dysfunction were found in acute liver failure models 28 and bile duct ligated rats with hyperammonemic diet.…”
Section: Discussionmentioning
confidence: 98%